Quantification of cracked area in thermal path of high-powermulti-chip modules using transient thermal impedance measurement - Eleffendi, Mohd. Amir; Yang, Li; Agyakwa, Pearl; Johnson, C. Mark (Elsevier, 2016)
Transient thermal impedancemeasurement is commonly used to characterize the dynamic behaviour of the heat flowpath in power semiconductor packages. This can be used to derive a “structure function”which is a graphical representation of the internal structure of the thermal stack. Changes in the structure function can thus be used as a non-destructive testing tool for detecting and locating defects in the thermal path. This paper evaluates the use of the structure function for testing the integrity of the thermal path in high powermulti-chipmodules. A 1.2 kV/200 A IGBT module is subjected to power cycling with a constant current. The structure function is used to estimate the level of disruption at the interface between the substrate and the baseplate/case. Comparison with estimations of cracked area obtained by scanning acoustic microscopy (SAM) imaging shows excellent agreement, demonstrating that the structure function can be used as a quantitative tool for estimating the level of degradation. Metallurgical cross-sectioning confirms that the degradation is due to fatigue cracking of the substrate mount-down solder.